Transformasi Mitos dalam Fiksi Horor Digital Indonesia: Analisis Struktural Kafan Hitam - Damra, Zulfardiana; Merawati, Fitri (Jurnal Bahasa dan Sastra, 2026)
This study examines the myth structure in Ramdani Abdul's digital novel Kafan Hitam through the perspective of Levi-Strauss's Structuralism. Unlike previous studies that focused on myths in oral traditions, this study applies Levi-Strauss's structural framework to a 198-chapter digital novel corpus on the GoodNovel platform. This study aims to identify the mythemes and binary oppositions that shape the pattern of mythic meaning in the story. The method used is qualitative descriptive with an in-depth search of the 198 novel chapters published on the GoodNovel platform. The data were analyzed by grouping the mythemes into four myth structures, the results of the study indicate that the most dominant cosmological structure (34 myths) significantly exceeds the geographical (8), sociological (10), and techno-economic (7) structures. It shows the relationship between humans and supernatural powers as the center of horror construction and local cultural representation. These findings indicate that Levi-Strauss's structural model remains productive beyond oral traditions and is capable of analyzing myths in contemporary digital literary platforms.